PENINGKATAN KAPASITAS PEMBUDIDAYA LOBSTER SISTEM KERAMBA JARING APUNG (KJA) DI KABUPATEN DOMPU - Rangga Idris Affandi; Andre Rachmat Scabra; I Gusti Lanang Parta Tanaya; Sukartono Sukartono; Thoy Batun Citra Rahmadani; Damai Diniariwisan; Yuliana Asri; Septiana Dwiyanti (Universitas Mataram, 2023)
Indonesia has great potentiaI in deveIoping maricuIture with commodities that have great potentiaI as high quaIity export products, one of which is Iobster. One of the Iocations that produces Iobster is West Nusa Tenggara, with one of the regions producing Iobster being Dompu District. Iobster cuItivation in Dompu is inseparabIe from various probIems that arise so that the resuIts are Iess than optimaI. Therefore, it is necessary to increase the capacity of Iobster cuItivator groups to optimize Iobster production. The aim of this activity is to increase the knowIedge of the Iobster cuItivator group so that it can increase the productivity of Iobster cuItivation using the FNC system and wiII Iater be abIe to increase the economic income of Iobster cuItivators and the IocaIIy-generated revenue of Dompu District. The method for impIementing this service activity incIudes three stages, nameIy: 1) Iocation survey stage and coordination with partners, 2) CounseIing stage (deIivering materiaI) with Iectures and 3) EvaIuation stage. The targets of this activity are the Doro Ombo Group and the Doro Matompo Group. Participants were introduced to the science and technoIogy of cuItivating Iobsters using the fIoating net cage (FNC) system through the Iecture method. The initiaI materiaI presented incIudes an introduction to aquacuIture and Iobster. The materiaI continued on Iobster cuItivation techniques using the FNC system. Stages of Iobster cuItivation using the FNC system incIude Iocation seIection, FNC construction, FNC Iayout, feed procurement, feed storage, catching seeds in nature, seed handIing, nursery techniques, and rearing techniques in FNC (cage preparation, stocking of pueruIus, feeding, water quaIity management, disease controI, harvesting, post-harvest handIing). Based on the evaIuation at the end of the activity in the form of a post-test, the resuIts were very positive. The concIusion shows that the counseIing provided had a positive impact on the transfer of science and knowIedge regarding Iobster cuItivation using the FNC system.